1999
DOI: 10.1007/s100500050215
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of f 0 observation in low energy pp collisions

Abstract: Abstract. Within the meson-exchange model we calculate f0-meson production cross section in πN and N N reactions and investigate the possibility for f0 observation via the KK decay mode in pp collisions. Our studies indicate that an extraction of the f0 signal is unlikely due to the large background from other reaction channels.PACS. 13.75.Cs Nucleon-nucleon interactions -13.75.Gx Pion-baryon interactions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…[34] since our studies in Ref. [50] have indicated that the multiplicity of scalar mesons in pp reactions is very small in the energy regime of interest.…”
Section: Dilepton Productionmentioning
confidence: 92%
“…[34] since our studies in Ref. [50] have indicated that the multiplicity of scalar mesons in pp reactions is very small in the energy regime of interest.…”
Section: Dilepton Productionmentioning
confidence: 92%
“…In fact, up to now in these reactions there has not been found any signal of these particles. The theoretical estimations result in negligible cross sections for the pp → f 0 pp → K + K − pp resonant contribution with respect to the non-resonant one [37] (the upper limit of the cross section for this reaction is estimated to be about 1 × 10 −4 nb/MeV at Q = 5 MeV and 4 × 10 −2 nb/MeV at 50 MeV [37]). Also the branching ratios of f 0 (980) and a 0 (980) are very poorly known.…”
Section: Description Of the Final State Interaction In The Ppkmentioning
confidence: 97%
“…According to Ref. [37] for energies up to Q = 115 MeV (DISTO measurement [19]) the production of resonant K + K − pairs should not produce any significant enhancement in the K + K − invariant mass.…”
Section: Description Of the Final State Interaction In The Ppkmentioning
confidence: 99%
“…This approach has been used in the investigation of the FSI of mesons in different processes in order to get a better understanding of the nature of the meson resonances as shown in Refs. [24][25][26][27] It has been suggested that the Λ(1405) could play an essential role on the kaon pair production through the pp → pK + (Λ(1405) → K − p) process [28] and this process seems more important than the contributions from the scalar mesons [11,29]. Indeed, the role played by the Λ(1405) state is crucial for reproducing the K − p mass distribution [12,30].…”
Section: Introductionmentioning
confidence: 99%